Application of Three-Dimensional Printing Technology for Improved Orbital-Maxillary-Zygomatic Reconstruction. Issue 2 (March 2019) - Xue, Runqi; Lai, Qingguo; Sun, Shaolong; Lai, Lei; Tang, Xiaopeng; Ci, Jiangbo; Zhang, Zhichao; Wang, Yang
Abstract : Abstract: The reconstruction of orbital-maxillary-zygomatic complex (OMZC) on patients suffering from trauma and space-occupying lesions is challenging due to the irregularity of craniomaxillofacial bones. To overcome the challenge in precise OMZC reconstruction, individual three-dimensional (3D) disease models and mirror-imaged 3D reconstruction models were printed on the basis of the computer tomography. Preoperative planning by rehearsing surgical procedures was made on the 3D disease models and the scaffolds including titanium and absorbable meshes or plates were anatomically premolded using the mirror-imaged 3D models as guide. Many benefits were achieved including more precise OMZC reconstruction, fluent and smooth procedures of surgeries, shorter operation time, less blood loss, and improved cosmetic outcomes of craniomaxillofacial shapes. There were no complications such as diplopia, infection, foreign body reaction, exophthalmos, enophthalmos, disordered occlusal relationship, and hematoma. And patients were satisfied with the functional and esthetic outcome during the following-up time. Therefore, OMZC reconstruction can be optimized and successful through preoperative planning and premolded scaffolds with 3D printing bone model by computer-aid design and manufacturing.